2022
DOI: 10.1007/s10551-022-05237-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethical Commitment Reminder and Reciprocity in the Workplace on Misreporting

Abstract: Despite the pervasive use of ethics training by companies, research in management accounting has not considered the effectiveness of such training in curtailing managers’ misreporting. This study examines the effect of ethics training on misreporting as a reminder to raise the awareness of employees’ ethical commitment. Furthermore, this study investigates the extent to which reciprocity in the workplace affects managers’ misreporting. The results from an experiment involving 124 managers show that in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 101 publications
(135 reference statements)
0
1
2
Order By: Relevance
“…Commitment to ethics has no positive effect on the ability to detect fraud. This study could not confirm previous research (Dammak et al , 2022; Ferdiansah et al , 2022; Rifai and Mardijuwono, 2020). It may cause an auditor with experience to be more responsive in detecting fraud.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Commitment to ethics has no positive effect on the ability to detect fraud. This study could not confirm previous research (Dammak et al , 2022; Ferdiansah et al , 2022; Rifai and Mardijuwono, 2020). It may cause an auditor with experience to be more responsive in detecting fraud.…”
Section: Discussioncontrasting
confidence: 96%
“…Commitment to ethics has no positive effect on the ability to detect fraud. This study could not confirm previous research (Dammak et al, 2022;Ferdiansah et al,…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…It would be worthwhile to explore more in-depth whether such a concept can improve the effect of codes of conduct on corrupt behavior. A recent study by Ferdiansah et al (2022) has found that the use of ethical commitment reminders can be used as an effective management control tool to deter unethical behaviors such as misreporting. Future studies can replicate this study in the context related to employees' corrupt behavior.…”
Section: Avenues For Future Researchmentioning
confidence: 99%
“…Unethical behaviour, such as corruption, fraudulent financial reporting, or misreporting by organisations has attracted scholarly attention from accounting researchers and other disciplines (see e.g. Cardinaels & Jia, 2016;Changwony & Paterson, 2019;Chong & Wang, 2019;Everett, Neu & Rahaman, 2007;Ferdiansah, Chong, Wang & Woodliff, 2022;Free and Murphy, 2015;Hunt, Curtis & Rixom, 2022;Jeppesen, 2019;Jia, Lent & Zeng, 2014;Kroos, Schabus & Verbeeten, 2022;Maas & Yin, 2022;Mayhew & Murphy, 2014;Rabl, 2011;Van Vu, Tran, Van Nguyen & Lim, 2018). Understanding how and why unethical behaviours occur and how they can be prevented is an essential managerial issue.…”
mentioning
confidence: 99%